A review of 'psychology and the study of education: critical perspectives on developing theories'. Issue 2 (3rd April 2019) - Dwyer, Christopher P.
Abstract : This review examines Psychology and the Study of Education: Critical Perspectives on Developing Theories, a collection of academic articles edited by Cathal Ó Siochrú. The collection comprehensively considers wide-ranging topics pertinent to the psychology of education, with a target audience of educators and students wishing to learn more about psychology. The review evaluates the collection as an integrated work of entries and analyses each component chapter; recognising the success of the collection with respect to its aim of challenging readers to critically reflect upon and consider the value of psychology in both understanding and influencing education. The book transcends the common formula of academic article collections in this area by being presented in a somewhat conversational manner, making it both interesting and accessible. The book is recommended for anyone interested in the psychology of education and for anyone who values the advancement of learning and teaching.